Analysis of the numerical simulation of a tilted heterogeneous reservoir using the black oil model - Santos, Guilherme; Souza, Marlon (Latin American Journal of Energy Research, 2026)
Numerical simulation is a fundamental tool for reservoir engineering, as it allows the optimization of production in hydrocarbon reservoirs. This study aims to analyze the dynamic behavior of a heterogeneous reservoir using the three-phase Black Oil model, through the open source simulator Open Porous Media (OPM Flow), with the visualization of the results through the ResInsight software. The model used was SPE9. Composed of 25 producing wells and 1 water injection well, covering a Cartesian grid of 9,000 blocks, with top depths ranging from 9,000 and 10,216 feet and with a porosity of 0.08 to 0.17. The methodology used was divided into 3 stages: pre-processing, processing and post-processing, with the implementation of mass conservation laws and Darcy's law. The numerical model was discretized by finite volumes and solved by Newton's method. The analysis of the results showed variations in pressure over the simulation time. The results show the importance of simulation for decision-making in reservoir engineering.
Keywords: reservoir simulation; Petroleum